Molecular basis for human respiratory syncytial virus transcriptional regulator NS1 interactions with MED25 - Kalita, Parismita; Khatavkar, Oam; Uwase, Grace; Korshunova, Yulia; Hu, Yuying; Wagner, Nicole D.; Xu, Jian; Pan, Jiehong; Nix, Jay C.; Gross, Michael L.; Brody, Steven L.; Borek, Dominika; et al. (Nature communications, 2025)
The Mediator complex facilitates interactions between transcription factors and RNA polymerase II, a process that is required for host gene transcription, including in response to viral infections. Among the many subunits in the Mediator complex, the MED25 subunit has been shown to be a target for viral activators during infection. Here we provide the molecular basis for the interaction between human respiratory syncytial virus (hRSV) nonstructural 1 protein (NS1) and the activator interaction domain (ACID) of MED25. The X-ray crystal structure of the complex revealed that NS1 straddles and binds two faces of MED25 ACID. This interaction is distinct from previously known viral activators. Importantly, our data support the conformational flexibility of viral transcriptional regulators. Furthermore, ChIP-seq and RNA-seq analysis identified the ATF3 transcription factor and a role for NS1/Mediator/ATF3 interaction in host gene regulation in hRSV infections. Our findings provide a molecular basis for hRSV NS1-based regulation of host gene transcription and reveal how viruses exploit the conformational heterogeneity at fuzzy transcription activator interfaces. This study provides the structural and biochemical characterization of the RSV NS1/MED25 ACID complex, revealing how RSV exploits fuzzy interfaces between coactivators and transcription factors, including ATF3, to modulate host gene transcription.